EL PODCAST PERIODÍSTICO COMO HERRAMIENTA DE COMUNICACIÓN ESTRATÉGICA A TRAVÉS DE LA PLATAFORMA DE YOUTUBE - ALARCON JIMENEZ, INGRID GABRIELA (2024)
This research project focuses on the analysis of journalistic podcasts as a strategic communication tool, especially through the YouTube platform, which has a great impact on the innovative combination of formats and platforms that have influenced distribution and reception of informative content. This study examines the distinctive characteristics of the journalism podcast and how its format allows for deeper and more personalized storytelling, which also highlights its ability to address complex topics in a unique and accessible way while encouraging active audience participation. Subsequently, the strategic choice of using YouTube as a platform for the dissemination of the podcast is delved into. In addition, the public's perception of journalistic podcasts hosted on the YouTube platform in comparison with traditional news sources is analyzed. Finally, this study presents implications and recommendations for journalism professionals and communication students interested in using podcasts as a strategic tool in journalism, leveraging the YouTube platform as a cash distribution channel. The purpose of this comprehensive analysis is to contribute to the understanding of how a journalistic podcast, strategically implemented on the YouTube platform, can improve communication, public participation and the dissemination of relevant information in the digital age.